Entrepreneurship performance of Vietnam - Nguyen Thi Thu Ha; Lam Ba Hoa (Serbian Journal of Management, 2022)
The study aims to measure entrepreneurship performance of Vietnam in comparison to Asiancountries by applying the Global Entrepreneurship Development Index (GEDI) and then employedthe Penalty for Bottleneck (PFB) methodology to allocate priority policies for the improvement ofentrepreneurship performance in Vietnam. Specifically, the GEDI consisting of three sub-indices:Entrepreneurial Attitudes, Entrepreneurial Abilities and Entrepreneurial Aspiration, which aredivided into 14 pillars and further subdivided into 28 variables, is used to identify the best and worstperforming variables of the GEDI in Vietnam in comparison to Asian countries. Then the PFBmethodology provides a more realistic analysis, aiming to discover bottle-neck factors, which arepoorly performing system components before suggesting recommendations to achieve the greatestimprovement of entrepreneurship performance in Vietnam. The results indicate that ten bottlenecksof 14 pillars are poorly performing with very low scores in Vietnam, in which the top priority policyis given for five pillars, including Risk acceptance, Opportunity perception, Internationalization,Technology absorption and Process innovation.